Impact of Soundbox by Third Party Application Providers (UPI) on Retailers, with Special Reference to Greater Chennai Corporation - Denny Jones B; Dr. M. Muruganandam (Journal of Corporate Finance Management and Banking System, 2024)
Before the advent of UPI, payments primarily relied on debit and credit cards, proving advantageous for medium-scale business retailers while disadvantaging small-scale or micro retailers using cash due to the high cost of POS machines. The introduction of the UPI digital payment system by the National Payments Corporation of India in 2016 marked a significant boon for customers and retailers of all types. Despite its benefits, some retailers hesitated due to perceived authenticity issues in receiving payments. However, since 2019, the third-party application provider Paytm revolutionized UPI adoption by proposing the installation of a soundbox. This innovative addition led to increased UPI utilization by retailers, driven by enhanced security, user-friendliness, simplified transactions, and lower monthly rental costs. This paper explores the impact and role of the soundbox post-installation by third-party application providers, examining its merits, demerits, and gauging retailers' perspectives on this transformative technology.